ENT300 Fundamental of Entrepreneurship. Business Plan : BOWL-O-CITY / Ahmad Amirul Ahmad Kamal...[et al.] - Ahmad Kamal, Ahmad Amirul; Delia, Evodius Dexter; Badar, Mohd. Rendy; Juni, Syafeqa Adeera; Usman, Muhammad Hasrul (2015)
BOWL-O-CITY is a formed on a business partnership agreement. A business partnership is the collaboration among the member who agrees to carry on an enterprise; contribute to it by combining property, knowledge, or activities; and share its profit. BOWL-O-CITY consists of five member and each member contributed in a certain amount of capital for as agreed in the company business agreement. The business will start on 1st of January 2016. All the five members of our business are required to participate in the business as agreed on the partnership contract and it was decided that Ahmad Amirul Bin Ahmad Kamal will be the manager of BOWL-O-CITY Company. Evodius Dexter Delia as the Marketing Manager, Syafeqa Adeera Binti Juni as the Administration Manager, Mohd. Rendy Bin Mohd. Badar as the Operation Manager and last but not least, Mohd. Hasrul Bin Usman as the Financial Manager of BOWL-O-CITY. Our business is in entertainment industry and we provide variety of activities other than bowling such as darts, pools and food and beverages lounge. Our services consist bowling, darts, pools and food and beverages lounge with the best premium quality of services and a luxury environment. We are ensuring all of our customers are fully satisfied with our entertainment and services. The pricing for our products and services are rated at reasonable prices as we would like to give proper services to our customer and we are not committed in taking advantage of our customers.